Mathematical simulation of infocommunication networks applying chaos theory - Karpukhin, A.; Gritsiv, D.; Tkachenko, A. (LUBLIN–RZESZOW, 2014)
The advent and wide usage of computer networks as well as an increasing number of various network services have resulted in the fact that the network traffic has become more complex and unpredictable. These properties have become especially apparent with the appearance of highspeed data transmission technology. It is connected with the fact that one of the main quality indeces (QoS) of operation of packet transmission networks is the number of lost packets. The loss of packets results to additional network traffic and, finally, “congestions”. At high speeds of data transmission packet losses, expressed in portions of a per-cent, lead to considerable information losses.
Keywords: chaos; dynamic systems; self-similarity; TCP/IP